A methodological proposal for planation surfaces mapping - José Roberto Mantovani; Guilherme Taitson Bueno (Revista Brasileira de Geomorfologia, 2022)
A mapping methodology of planation surfaces based on automated altimetric stratification is proposed in this work. In this methodology, mathematical concepts related to the variation of the function of pixels frequency vs. altitude are used to obtain the grouping of relief forms. The automatic clustering allows to distinguish the planation surfaces from elevation without the interference of decision maker. The input data for the execution of the mapping algorithm is the variation of elevation as a function of the number of pixels, extracted from SRTM data. The mapping of planation surfaces and the validation of computational algorithm were carried out for an area located in the municipality of Chapada Gaúcha, Minas Gerais State, Brazil, which presents two planation surfaces recognized in the literature. The landforms in the study area were associated with three planation cycles, interpreted as corresponding to King’s Post-Gondwana, South American and Velhas surfaces. Remaining (reserved) and dissected landforms from South American and Velhas surfaces were mapped, while for Post-Gondwana surface only dissected landforms were identified. The mapped surfaces showed an important correlation with the regional soil types, indicating that the spatial distribution of surficial formations is directly related to the distribution of the planation surfaces. The results showed that the proposed algorithm can automatically reveal the relief organization of a region, indicate characteristics of the planation surfaces such as the degree of flatness and leveling, in addition to helping to understand the relationship between landforms and soil distribution. The method is suitable for tectonically stable not-tilted reliefs and for areas of stepped planation surfaces. The method is suitable for stepped landsurfaces located at tectonically stable and not-tilted areas.